Reconstruction of Tolaki and Moronene Language Vocal Protophonemes - Mustamar, Wawan Marhanjono; Mbete, Aron Meko; Dhanawaty, Ni Made; Budasi, I Gede (e-Journal of Linguistics, 2019)
The Tolaki language and the Moronene languages are part of the Austronesian language group. The reconstruction is done based on the hypothesis of a genetic relationship and regularity. Historical comparison methods were used in this study. The purpose of the reconstruction was to obtain accurate results on the assessment of language relations. It is deemed necessary to reconstruct the proto in order to seek the evidence of the retention and innovation that occur in the two respective languages. From the reconstruction, several findings and proofs were generated, which among others are TlM vocal proto-phonemes: * a, * i, * u, * e, and * o; PTlMr * a are found at the beginning, middle and the end of the word. The proto-phonemes are 1) * a (a-, -a-, -a)> Tl, Mr a, 2) PTlMr * i (i- -i- -i)> Tl, Mr i, 3) PTlMr * u (u -, -u-, -u)> Tl, Mr u, 4) PTlMr * e (e-, -e-, e-)> Tl, Mr e, and 5) PTlMr * o (o-, -o-, o-)> Tl Mr o.